2021
DOI: 10.1002/ca.23770
|View full text |Cite
|
Sign up to set email alerts
|

The persistent median artery and its vascular patterns: A meta‐analysis of 10,394 subjects

Abstract: The presence of a persistent median artery (PMA) has been implicated in the development of compression neuropathies and surgical complications. Due to the large variability in the prevalence of the PMA and its subtypes in the literature, more awareness of its anatomy is needed. The aim of our meta-analysis was to find the pooled prevalence of the antebrachial and palmar persistent median arteries. An extensive search through the major databases was performed to identify all articles and references matching our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 74 publications
0
24
0
4
Order By: Relevance
“…In this article, we introduced the CATAM rubric and used it to critically appraise a recently published anatomical MA (Kacprzyk et al, 2020). There have been other anatomical MAs recently published (Aldabe et al, 2019; Bellier et al, 2020; Berthaume & Bull, 2021; Cheruiyot et al, 2021; Dreher et al, 2018; Graves et al, 2017; Harvie et al, 2019; Koziej et al, 2020; Morelli et al, 2019; Nallikuzhy et al, 2018; Roberts et al, 2021; Sirico et al, 2019; Solewski et al, 2021; Stefura et al, 2018; Tomaszewska et al, 2018; Tomaszewska et al, 2018; Tomaszewski et al, 2017; Tomaszewski et al, 2017; Vikse et al, 2016a, 2016b; Whitley et al, 2020; Yammine, 2013, 2014b, 2014c, 2014d; Yammine et al, 2015; Yurasakpong et al, 2021). We believe that the running paper that we used is an exemplary anatomical MA (Kacprzyk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we introduced the CATAM rubric and used it to critically appraise a recently published anatomical MA (Kacprzyk et al, 2020). There have been other anatomical MAs recently published (Aldabe et al, 2019; Bellier et al, 2020; Berthaume & Bull, 2021; Cheruiyot et al, 2021; Dreher et al, 2018; Graves et al, 2017; Harvie et al, 2019; Koziej et al, 2020; Morelli et al, 2019; Nallikuzhy et al, 2018; Roberts et al, 2021; Sirico et al, 2019; Solewski et al, 2021; Stefura et al, 2018; Tomaszewska et al, 2018; Tomaszewska et al, 2018; Tomaszewski et al, 2017; Tomaszewski et al, 2017; Vikse et al, 2016a, 2016b; Whitley et al, 2020; Yammine, 2013, 2014b, 2014c, 2014d; Yammine et al, 2015; Yurasakpong et al, 2021). We believe that the running paper that we used is an exemplary anatomical MA (Kacprzyk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sugimoto et al (1994) explained that the PMA provides more sustainable blood perfusion to the MN than its "normal" vascularization patterns. Solewski et al (2021)…”
Section: Discussionmentioning
confidence: 99%
“…A PMA accompanies a BMN in many reports of CTS. Solewski et al (2021) conducted a meta‐analysis on the prevalence of PMAs and reported that the overall prevalence of palmar type PMA was 8.6% (95% CI: 6.7–10.8) and antebrachial type 34.0% (95% CI: 14.5–56.5). The antebrachial PMA is usually asymptomatic and detected during cadaveric dissection or radiological examination or surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antebrachial type is a delicate remnant of a partial regression of the median artery that terminates proximal to the wrist in the antebrachium while serving as the primary blood supply to the median nerve [5]. Previous reports indicate a PMA prevalence of 4.2%-6.6% with the antebrachial PMA making up nearly 75% of those cases [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%